Beyond code-switching and translanguaging: fluidity and fixity in everyday language practices of multilingual Singapore - Chew, Amber Si Hui (Nanyang Technological University, 2023)
In multilingual Singapore, language mixing is an everyday phenomenon that can be observed in the speech of many Singaporeans, especially in informal and private settings (Bolton & Botha, 2019; Botha, 2021; Tay, 1989). Among the existing studies that have analysed language mixing in the Singaporean community, most utilise a code- switching approach (e.g. Kamwangamalu & Lee, 1991; Lee, 2003, 2019a, 2019b; Sumartono and Tan, 2018; Tay, 1989). However, the way that a code-switching approach frames mixed language practices may be rather limiting, especially in the case of language communities as diverse as Singapore. One of the key problems in applying a code-switching approach to multilingual Singaporean data is the difficulty in delineating the boundaries between two or more languages/codes/varieties, as has been highlighted in studies such as Alsagoff (2010), Leimgruber (2012), Li (2018), and Tay (1989). As an alternative approach to analysing Singaporean data, Li (2018) proposes the use of translanguaging, a concept that has garnered interest in recent years. This thesis will assess the strengths and weaknesses of both models of code-switching and translanguaging as possible approaches to analysing Singaporean speech data. As part of the data for the analysis, naturalistic conversation data was collected from 10 friendship groups each consisting of 2 to 5 Singaporean adult participants between 21-35 years old. Participants were asked to converse normally with each other for about an hour without any specific set topic, with an audio recorder placed in the room without the researcher present. Data playback sessions with some participants were also conducted as follow-up interviews to supplement the analysis. With a code-switching approach, various instances of linguistic hybridity that were present in the data made it difficult to categorise utterances into corresponding linguistic codes and varieties, which is a common premise in conventional code-switching analyses. Furthermore, some patterns of hybridity seen in the data challenges separatist notions of language, an assumption which many code-switching analyses take. On the other hand, while translanguaging proved to be a rather effective approach in addressing abovementioned linguistic hybridity, it makes the central assumption that language boundaries and ‘named languages’ are arbitrary constructs that are unrepresentative of how multilinguals communicate with each other (Garcia & Li, 2014; Otheguy, Garcia, & Reid, 2015). This was ultimately a key shortcoming of translanguaging that failed to account for instances where speakers showed an awareness or adherence to these language boundaries in their language practices. As such, both code- switching and translanguaging approaches were found to be inadequate in accounting for the complexities of Singaporean speech data, which exhibited both fluidity and fixity (Jaspers & Madsen, 2019) as important aspects of speakers’ linguistic behaviour. Fluidity and fixity were found to be intrinsically linked to and influencing each other as mutually presupposing concepts in Singaporean speech, resulting in seemingly contradicting ideologies and linguistic behaviour observed in the data. The findings from this thesis allow for a closer look into the “messier” realities of the purported intergenerational language shift from local vernaculars to English among the younger adult generation of Singaporeans (Bokhorst-Heng & Silver, 2017), and sheds light on how these individuals navigate their language choices in practice amidst an often conflicting and complex web of linguistic ideologies that are omnipresent in their everyday lives.